Halogen-free flame-retardant ABS (acrylonitrile butadiene styrene) material as well as preparation method and application thereof
By introducing SAN resin and halogen-free flame retardant into ABS materials and controlling the physical properties of ABS resin, the appearance problems and flame retardant problems of ABS materials after laser marking are solved, and high pencil hardness and gloss are achieved Comprehensive effect of flame retardant at level V-2 or above.
Patent Information
- Application Number
- CN202411738246.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing ABS materials have problems of decreasing gloss, burning, yellowing and black after laser marking, and cannot achieve halogen-free flame retardant at level V-2 or above.
By introducing SAN resin and specific contents of halogen-free flame retardant, and controlling the melt flow rate and cantilever beam notch impact strength, a halogen-free flame retardant ABS material with high pencil hardness and high gloss is formed.
It achieves the high pencil hardness and gloss of the material, and has halogen-free flame retardant at level V-2 or above, and has good laser marking effect, so the marking is not easily worn.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and more specifically to a halogen-free flame-retardant ABS material and a preparation method and application thereof. Background Art
[0002] Laser marking is a marking method that uses high-energy-density lasers to locally irradiate the workpiece, causing the surface material to vaporize or undergo a chemical reaction that causes a color change, thereby leaving a permanent mark.
[0003] ABS resin is a ternary graft copolymer of acrylonitrile-butadiene-styrene, which has mechanical properties of rigidity and toughness balance, excellent chemical resistance, low temperature resistance and dimensional stability, and is easy to process and shape. Therefore, ABS resin is widely used in the fields of home appliances, electronics and automobiles. However, the surface hardness of ABS products is relatively low, with a pencil hardness of only 2B~B. After being laser marked, the glossiness of ABS products decreases, and they even have appearance problems such as being burnt, yellowed and blackened. In order to improve such appearance problems, a large amount of polymethyl methacrylate (PMMA) is usually added to the resin composition in the prior art.
[0004] For example, the patent CN104804360A discloses an impact-resistant ABS resin composition for white laser marking and its preparation and application, which comprises ABS resin and PMMA in a mass ratio of (1-9): (1-9). Its acrylic structure effectively enhances the ability of the resin composition to foam when heated by laser radiation, so that the white mark printed by its laser has higher whiteness and better clarity. However, the flame retardancy of PMMA is relatively low, resulting in the flame retardancy of the ABS / PMMA alloy material failing to reach V-2 level. It is urgent to develop an ABS resin material suitable for laser marking, which has high pencil hardness and high gloss, and at the same time achieves halogen-free flame retardancy above V-2 level. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects and shortcomings of existing ABS materials that they cannot have the performance of high pencil hardness and high glossiness and have halogen-free flame retardancy above V-2 level, and to provide a halogen-free flame retardant ABS material.
[0006] Another object of the present invention is to provide a method for preparing a halogen-free flame-retardant ABS material.
[0007] Another object of the present invention is to provide an application of a halogen-free flame-retardant ABS material in the preparation of a laser-markable material.
[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0009] The present invention protects a halogen-free flame-retardant ABS material, comprising the following components in parts by weight:
[0010]
[0011] The melt flow rate (ASTM D1238) of the ABS resin at 220° C. and 10 kg is ≥5 g / 10 min, and the notched Izod impact strength (ASTM D256) is ≤380 J / m; the melt flow rate (ASTM D256) of the SAN resin at 220° C. and 10 kg is ≤40 g / 10 min.
[0012] The halogen-free flame-retardant ABS material of the present invention uses ABS resin as a base resin and introduces SAN resin, which can control the content of SAN in the entire ABS system, thereby greatly improving the rigidity, glossiness and chemical stability of the material, while avoiding the problems of poor compatibility and loss of mechanical properties caused by the introduction of heterogeneous resins. At the same time, a specific content of halogen-free flame retardant is compounded in the ABS material, so that the material can achieve flame retardancy of V-2 or above while ensuring mechanical properties; in addition, a certain amount of laser marking agent is added, so that the material can be efficiently laser marked; under the synergistic effect of various raw material components, the material has high pencil hardness and high glossiness, and has a good laser marking effect, and the mark is not easy to be worn and can be maintained for a long time.
[0013] Izod notched impact strength and melt flow rate are parameters that reflect the ratio of butadiene monomer in ABS resin. The main function of butadiene monomer in ABS resin is to improve the elasticity and toughness of the resin material. The higher the ratio of butadiene monomer, the higher the Izod notched impact strength and the lower the melt flow rate. Using ABS resin with specific Izod notched impact strength and melt flow rate is conducive to controlling the content of SAN in the entire ABS system when introducing SAN resin, so as to improve the rigidity, glossiness and chemical stability of the material.
[0014] The use of a mixed system of ABS high-rubber powder and SAN resin can also help control the content of SAN in the entire ABS system; however, the inventors found that the amount of ABS high-rubber powder required in the mixed processing of ABS high-rubber powder and SAN resin is relatively large, and excessive powder is prone to uneven feeding and bridging during extrusion granulation, and the product has poor uniformity and is not suitable for use in laser-markable materials. The present invention not only improves the processing performance by compounding ABS resin with a specific melt flow rate with SAN resin, but also prepares a material with high rigidity, glossiness and chemical stability.
[0015] In some embodiments, the ABS resin has a melt flow rate (ASTM D1238) of 5-45 g / 10 min at 220° C. and 10 kg, and an Izod notched impact strength (ASTM D256) of 150-380 J / m.
[0016] Preferably, the melt flow rate (ASTM D1238) of the ABS resin at 220° C. and 10 kg is 8-40 g / 10 min; preferably, the notched Izod impact strength (ASTM D256) of the ABS resin is 180-370 J / m; ABS resins meeting the above requirements include but are not limited to ABSDG-MG94, ABSDG-417 and ABSDG-MG29 series products of Tianjin Dagu Chemical Co., Ltd.
[0017] In some embodiments, the content of ABS resin that can achieve the purpose of the present invention can be 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts or any range therebetween.
[0018] In some embodiments, the mass fraction of the ABS resin in the halogen-free flame-retardant ABS material is ≥ 46%.
[0019] In some embodiments, the melt flow rate (ASTM D1238) of the SAN resin at 220° C. and 10 kg is 8-40 g / 10 min. Controlling the melt flow rate range of the SAN resin is beneficial to improving the hardness of the material and improving the mechanical properties of the material.
[0020] Preferably, the melt flow rate of the SAN resin at 220°C and 10kg (ASTM D1238) is 20-35g / 10min. ABS resins meeting the above requirements include but are not limited to: SAN 350NA of Kumho Sunny Plastics Co., Ltd. and SAN SA30 of LG Chemical (Huizhou) Chemical Co., Ltd.
[0021] In some embodiments, the content of SAN resin (styrene-acrylonitrile copolymer) that can achieve the purpose of the present invention can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts or any range therebetween.
[0022] In some embodiments, the mass fraction of the SAN resin in the halogen-free flame-retardant ABS material is ≥ 18%.
[0023] In some embodiments, the content of the halogen-free flame retardant that can achieve the purpose of the present invention can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 parts or any range therebetween.
[0024] In some embodiments, the halogen-free flame retardant includes a phosphorus-based flame retardant and / or a nitrogen-based flame retardant.
[0025] Preferably, the phosphorus-based flame retardant is selected from phosphate flame retardants; specifically, bisphenol A-bis(diphenyl phosphate) (BDP) is preferred.
[0026] Preferably, the nitrogen-based flame retardant is selected from ammonium salt flame retardants; specifically, melamine cyanurate (MCA) is preferred.
[0027] The present invention has no special requirements for the laser marking agent, and can be arbitrarily selected from conventional materials in the field of laser marking agents; including but not limited to black-to-white laser marking agents and white-to-black laser marking agents. Preferably, the laser marking agent is at least one of phthalocyanine salts, dioxazine series, anthraquinone series, periconazole series, carbon black, titanium black, iron oxide black, and surface alkylated modified silica.
[0028] Preferably, the phthalocyanine salt is copper phthalocyanine and / or aluminum phthalocyanine.
[0029] In some embodiments, the mass ratio of the ABS resin to the SAN resin is (1.0-3.0):1, preferably (1.2-2.6):1, and more preferably (1.5-2.5):1.
[0030] In some embodiments, the invention further comprises: 0.2-1 part of an antioxidant and 0.2-1 part of a processing aid.
[0031] Preferably, the antioxidant is composed of a hindered amine primary antioxidant and a phosphite auxiliary antioxidant.
[0032] More preferably, the hindered amine primary antioxidant is selected from antioxidant 1010;
[0033] More preferably, the phosphite auxiliary antioxidant is selected from antioxidant 168.
[0034] Preferably, the processing aid includes at least one of a lubricant, a dispersant, white mineral oil and a coupling agent.
[0035] More preferably, the lubricant is selected from zinc stearate.
[0036] More preferably, the coupling agent is selected from silane coupling agents.
[0037] The invention discloses a method for preparing a halogen-free flame-retardant ABS material, comprising the following steps: uniformly mixing various raw material components in a formula amount, and melt-blending and extruding to obtain the halogen-free flame-retardant ABS material.
[0038] In some embodiments, the melt extrusion temperature is 180-220°C.
[0039] In some embodiments, the preparation method of the halogen-free flame-retardant ABS material comprises the following steps: uniformly mixing the raw material components of the formula, and melt-extruding through a screw extruder at an extrusion temperature of 180-220° C., a rotation speed of 200-300 rpm, and a feeding rate of 200-400 kg / h to obtain the halogen-free flame-retardant ABS material.
[0040] The invention protects the use of a halogen-free flame-retardant ABS material in preparing a laser-markable material.
[0041] In some of the embodiments, the halogen-free flame-retardant ABS material is used in the preparation of electronic appliances or household appliances.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The present invention provides a halogen-free flame-retardant ABS material, which uses ABS resin as a base resin and introduces SAN resin at the same time, thereby increasing the proportion of SAN in the entire ABS system, greatly improving the rigidity, glossiness and chemical stability of the material, and avoiding the problems of poor compatibility and loss of mechanical properties caused by the introduction of heterogeneous resins. At the same time, a specific content of halogen-free flame retardant is compounded in the ABS material, so that the material can achieve flame retardancy of V-2 or above while ensuring mechanical properties; under the synergistic effect of various raw material components, the material has high pencil hardness and high glossiness, and has a good laser marking effect, and the mark is not easy to be worn and can be maintained for a long time. DETAILED DESCRIPTION
[0044] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0045] The raw materials used in the following examples and comparative examples are as follows:
[0046] ABS resin (acrylonitrile-butadiene-styrene terpolymer):
[0047] ABS resin 1: ABSDG-MG94, Tianjin Dagu Chemical Co., Ltd.; melt flow rate (ASTM D1238) at 220°C and 10 kg is 37 g / 10 min, and Izod notched impact strength (ASTM D256) is 190 J / m.
[0048] ABS resin 2: ABSDG-417, Tianjin Dagu Chemical Co., Ltd.; melt flow rate (ASTM D1238) at 220°C and 10 kg is 20 g / 10 min, and Izod notched impact strength (ASTM D256) is 200 J / m.
[0049] ABS resin 3: ABSDG-MG29, Tianjin Dagu Chemical Co., Ltd.; melt flow rate (ASTM D1238) at 220°C and 10 kg is 10 g / 10 min, and Izod notched impact strength (ASTM D256) is 360 J / m.
[0050] SAN resin (styrene-acrylonitrile copolymer):
[0051] SAN resin 1: SAN 350NA, Kumho Sunny Plastics Co., Ltd.; melt flow rate (ASTM D1238) at 220°C, 10 kg is 33 g / 10 min.
[0052] SAN resin 2: SAN SA30, LG Chemical (Huizhou) Chemical Co., Ltd.; melt flow rate (ASTM D1238) at 220° C., 10 kg is 29 g / 10 min.
[0053] SAN resin 3: SAN NX3400, manufactured by Taiwan Chemical Fiber Co., Ltd.; melt flow rate (ASTM D1238) at 220° C. and 10 kg is 10 g / 10 min.
[0054] SAN resin 4: SAN 320NA, Kumho Sunny Plastics Co., Ltd.; melt flow rate (ASTM D1238) at 220°C, 10 kg is 110 g / 10 min.
[0055] SAN resin 5: SAN SA50, LG Chemical (Huizhou) Chemical Co., Ltd.; melt flow rate (ASTM D1238) at 220° C., 10 kg is 55 g / 10 min.
[0056] Polymethyl methacrylate (PMMA): PMMA LG, Sumitomo Chemical Singapore Pte. Ltd.
[0057] Flame retardant: WSFR-PX-220, Zhejiang Wansheng Technology Co., Ltd.
[0058] Laser marking agent: Carbon black Ensaco 250G, Haiyi Company, Hong Kong, China.
[0059] Antioxidants: RIANOX 1010 and RIANOX 168 in a mass ratio of 1:1, from Rianlon Corporation.
[0060] Processing aid: EBS B50, PT.CMS CHEMICAL INDONESIA.
[0061] The preparation method of the halogen-free flame-retardant ABS material of the following examples and comparative examples comprises the following steps: uniformly mixing the raw material components of the formula, and melt-extruding through a screw extruder at an extrusion temperature of 200° C., a rotation speed of 250 rpm, and a feeding rate of 300 kg / h to obtain the halogen-free flame-retardant ABS material.
[0062] Examples 1 to 8
[0063] This embodiment provides a halogen-free flame-retardant ABS material, the components of which are shown in Table 1.
[0064] Table 1 Examples 1 to 8 (parts by weight)
[0065]
[0066] Comparative Examples 1 to 7
[0067] This comparative example provides a halogen-free flame-retardant ABS material, the components of which are shown in Table 2.
[0068] Table 2 Comparative Examples 1 to 7 (parts by weight)
[0069]
[0070]
[0071] Performance Testing
[0072] The halogen-free flame-retardant ABS material samples of Examples 1-8 and Comparative Examples 1-7 were tested for impact strength, pencil hardness, surface scratch resistance, glossiness, flame retardancy and laser marking effect. The test results are shown in Table 3.
[0073] Impact strength: Tested according to standard ISO 180.
[0074] Pencil hardness: Refer to the ASTM D3363 test standard. The specific method is: Make the ABS material sample into a 70mm×40mm×3mm square injection molded sample and place it on a fixed horizontal surface. The pencil is at a 45° angle to the coating (pointing in the opposite direction of the tester) and the pencil is pushed away from the tester to draw a 6.5mm long stroke. This process starts with the hardest pencil until the pencil does not scratch the sample surface. The corresponding pencil hardness is the sample pencil hardness.
[0075] Surface scratch resistance: The scratch resistance was evaluated using a friction color fastness tester: ABS material was used to prepare a 70mm×40mm×3mm square injection molded sample, which was rubbed back and forth 500 times with gauze, and the depth of the scratch was observed under a Leica microscope at 200 times. The shallower the scratch, the better, and the deeper the scratch, the worst. The evaluation was graded as follows: Worst -, Poor -, Ordinary 0, Better +, Best ++.
[0076] Gloss: Tested according to standard GB / T 8807-1988.
[0077] Flame retardancy: tested according to standard UL94.
[0078] Laser marking effect: The laser marking pattern is observed and evaluated under a Leica microscope at 200 times magnification; the clearer the edge of the laser engraving and the smoother the pattern, the better the laser marking effect; the evaluation grading of this test is: worst -, poor -, ordinary 0, good +, best ++. This test uses an ultraviolet marking machine, model UV-3X, with parameter conditions of 365nm, 3W.
[0079] Table 3
[0080]
[0081]
[0082] As shown in Table 3, the impact strength of the halogen-free flame-retardant ABS material of the present invention is ≥10KJ / m 2 The pencil hardness is above F level, the glossiness at 60° is above 90, the flame retardant level reaches V-2 level, and the surface scratch resistance and laser marking effect evaluation grades are both ++ level.
[0083] Compared with Example 1, in Comparative Example 1, no SAN resin is added, the pencil hardness is only B grade, the 60° glossiness decreases, and the surface scratch resistance and laser marking effect are poor.
[0084] Compared with Example 1, PMMA is used to replace SAN resin in Comparative Example 2. Although it has better surface scratch resistance and laser marking effect, the flame retardancy of PMMA is relatively low, resulting in the flame retardancy of the material failing to reach V-2 level.
[0085] Compared with Example 1, when ABS resin 3 with low melt flow rate and high Izod notched impact strength is used in Comparative Example 3, its pencil hardness is only HB grade, and the surface scratch resistance and laser marking effect are reduced.
[0086] Compared with Example 1, the pencil hardness, surface scratch resistance and laser marking effect of Comparative Examples 4-5 using SAN resin with a higher melt flow rate decreased.
[0087] Compared with Example 1, the amount of SAN resin added in Comparative Examples 6-7 is too low, and the pencil hardness, surface scratch resistance and laser marking effect cannot be effectively improved; when the amount of SAN resin added is too high, the impact strength is too low and the toughness is poor.
[0088] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A halogen-free flame-retardant ABS material, characterized in that: The composition includes the following components in parts by weight: The ABS resin has a melt flow rate of ≥5 g / 10 min at 220° C. and 10 kg, and an Izod notched impact strength of ≤380 J / m; The melt flow rate of the SAN resin at 220° C. and 10 kg is ≤40 g / 10 min.
2. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: The ABS resin has a melt flow rate of 8-40 g / 10 min at 220° C. and 10 kg, and an Izod notched impact strength of 180-370 J / m.
3. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: The melt flow rate of the SAN resin at 220° C. and 10 kg is 20-35 g / 10 min.
4. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: The mass ratio of the ABS resin to the SAN resin is (1.0-3.0):
1.
5. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: The halogen-free flame retardant includes a phosphorus-based flame retardant and / or a nitrogen-based flame retardant.
6. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: The laser marking agent is at least one of phthalocyanine salt, dioxazine series, anthraquinone series, peronone series, carbon black, titanium black, iron oxide black, and surface alkylated modified silicon dioxide.
7. The halogen-free flame-retardant ABS material according to claim 1, characterized in that: Also includes: Antioxidant 0.2-1 part, processing aid 0.2-1 part.
8. A method for preparing the halogen-free flame-retardant ABS material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: uniformly mixing the raw material components in the formula, and melting, blending and extruding to obtain the halogen-free flame-retardant ABS material.
9. The method for preparing a halogen-free flame-retardant ABS material according to claim 8, characterized in that: The melt extrusion temperature is 180-220°C.
10. Use of the halogen-free flame-retardant ABS material according to any one of claims 1 to 7 in preparing a laser-markable material.
Citation Information
Patent Citations
Anti-impact ABS resin composition for white laser mark and preparation and application thereof
CN104804360A
Halogen and phosphorus-free flame-retardant antistatic ABS resin and its preparation method
CN102936391A
High-weather-resistance laser marking ABS composite material with yellow background and black characters as well as preparation method and application of high-weather-resistance laser marking ABS composite material
CN116178881A
Laser marking resin composition
EP0708147A1